2014
DOI: 10.1186/1756-0500-7-272
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C virus infections among patients with chronic hepatitis at Bereka Medical Center, Southeast Ethiopia: a retrospective study

Abstract: BackgroundViral hepatitis exists throughout the world and is a major global public health problem affecting millions of people. Hepatitis B (HBV) and hepatitis C (HCV) virus are the commonest causes of inflammation of the liver leading to chronic liver disease, cirrhosis, hepatocellular carcinoma and even fulminant hepatitis. The objective of this retrospective study was to determine the prevalence of infections with HBV and HCV among patients with chronic hepatitis who visited Bereka Medical Center, southeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 5 publications
2
21
4
1
Order By: Relevance
“…However our current finding is lower when compared to study done on donors at Felege Hiwot referral hospital 25 % [ 17 ] Buseri et al Nigeria 18.6 % [ 27 ], Taye et al 22.3 % [ 28 ], Bereka Medical center, Southeast Ethiopia.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…However our current finding is lower when compared to study done on donors at Felege Hiwot referral hospital 25 % [ 17 ] Buseri et al Nigeria 18.6 % [ 27 ], Taye et al 22.3 % [ 28 ], Bereka Medical center, Southeast Ethiopia.…”
Section: Discussioncontrasting
confidence: 78%
“…From our study, the prevalence rate of HCV was 0.4 %, this is low when compared with 3.1 % in Sudan [ 15 ], Tessema et al 0.7 % [ 7 ], Baye et al 1.7 % [ 10 ], Dessie et al 13.3 % [ 17 ], Wasfi and Sadek among Egyptian donors (3.5 %) [ 6 ], Yohannes Zenebe et al 0.6 % [ 29 ] among pregnant women, 0.9 % prevalence among population and 1.3 % among adults over 15 years old [ 30 ] 0.8 % [ 25 ], Anagaw et al 1 % among medical waste handlers [ 22 ], Bekele Sharew et al 0.61 % [ 21 ], and Taye et al 3.6 % [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-regression plots for the mean age group and study years were presented in Additional file 4. Similarly, many studies in symptomatic liver disease patients reported HBsAg detection ranging from 9.9 to 35.8% [4451] with a median prevalence of 21.2% (IQR = 13.4–33.6) (Table 2). The meta-analysis estimate among these patients also showed 20.0% (95%CI: 15.0–26.1) (Additional file 5).…”
Section: Resultsmentioning
confidence: 80%
“…A similar variation was also reported, among other groups, such as VCT clients [10–12], diabetic patients [58], antenatal care (ANC) [39] and medical waste handlers [32] (Table 4). Likewise, the magnitude of anti-HCV antibody from chronic liver disease patients showed a variable prevalence rate over time with high (37.8%) in 1995 [49] and low (2.7%) in 2014 [51] (Table 4). For the HCV meta-analysis, 24 (75.0%) studies were eligible and selected from the total of 32 studies (Additional file 2).…”
Section: Resultsmentioning
confidence: 99%
“…Viral hepatitis is an inflammation of the liver that leads to chronic liver disease, liver cirrhosis, and hepatocellular carcinoma and finally, may cause fulminant hepatitis. Hepatitis B is one of the most common viral hepatitis in addition to hepatitis C [1] . Hepatitis B is one of the popular health problems and is considered as a major global infectious hazard.…”
Section: Introductionmentioning
confidence: 99%